Student’s attitudes Toward the Personality Competencies of Guidance and Counseling Teacher’s at SMP Negeri 27 Medan - Violina, Erwita Ika; Sumbayak, Agnes Viola (Jurnal Tematik, 2025)
This study aims to determine the attitudes of students at SMP Negeri 27 Medan towards the personality competencies possessed by guidance counselors. This study uses a quantitative approach. The sampling technique used is simple random sampling. The population of this study was all 7th and 8th grade students of SMP Negeri 27 Medan, totaling 500 students. The research sample consisted of 222 7th and 8th grade students at SMP Negeri 27 Medan. Data were collected through a student attitude scale, then analyzed using descriptive statistics available in SPSS. The results show that student attitudes are in the sufficient category. There are five aspects that are the focus of this study. In addition, the results obtained are no significant differences between the attitudes of men and women. This indicates that the attitudes of men and women towards the personality competencies possessed by guidance counselors tend to be the same and do not have differences.